Women Benefit More Than Men in Response to College-based Meditation Training - Rojiani, Rahil; Santoyo, Juan F.; Rahrig, Hadley; Roth, Harold D.; Britton, Willoughby B. (Frontiers in Psychology, 2017)
Objectives: While recent literature has shown that mindfulness training has positive effects on treating anxiety and depression, there has been virtually no research investigating whether effects differ across genders— despite the fact that men and women differ in clinically significant ways. The current study investigated whether college-based meditation training had different effects on negative affect for men and women. Methods: Seventy-seven university students (36 women, age = 20.7 ± 3.0 years) participated in 12-week courses with meditation training components. They completed self-report questionnaires of affect, mindfulness, and self-compassion before and after the course. Results: Compared to men, women showed greater decreases in negative affect and greater increases on scales measuring mindfulness and self-compassion. Women’s improvements in negative affect were correlated to improvements in measures of both mindfulness skills and self-compassion. In contrast, men showed non-significant increases in negative affect, and changes in affect were only correlated with ability to describe emotions, not any measures of experiential or self-acceptance. Conclusions: These findings suggest that women may have more favorable responses than men to school-based mindfulness training, and that the effectiveness of mindfulness-based interventions may be maximized by gender-specific modifications.